2012
DOI: 10.1111/j.1471-0528.2012.03401.x
|View full text |Cite
|
Sign up to set email alerts
|

Abuse from in‐laws and associations with attempts to control reproductive decisions among rural women in Côte d’Ivoire: a cross‐sectional study

Abstract: Objective To document the lifetime prevalence of abuse from in-laws (both nonphysical maltreatment and physical violence), the forms of in-law abuse and reproductive control, and the relationship between experiences of in-law abuse and reproductive control among partnered women in rural Cô te d'Ivoire.Design Cross-sectional study using baseline data (October 2010) from a randomised controlled trial examining socio-economic interventions on reduction of violence against Ivorian women.Population A total of 981 I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
54
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(56 citation statements)
references
References 32 publications
2
54
0
Order By: Relevance
“…In some situations the in-law family can exert a profound degree of control over their daughter-in-law’s life if she is slow to conceive or does not conceive 45. This may consist of forcing a woman to abandon use of contraception, or telling their son to leave her, have a baby with someone else or otherwise to punish her through emotional or physical abuse.…”
Section: Reproductive Control Perpetrated By the Wider Familymentioning
confidence: 99%
“…In some situations the in-law family can exert a profound degree of control over their daughter-in-law’s life if she is slow to conceive or does not conceive 45. This may consist of forcing a woman to abandon use of contraception, or telling their son to leave her, have a baby with someone else or otherwise to punish her through emotional or physical abuse.…”
Section: Reproductive Control Perpetrated By the Wider Familymentioning
confidence: 99%
“…Recent studies in Côte d'Ivoire and Jordan indicate that, not only do the concept of reproductive coercion and the association between these behaviors and poor reproductive health appear to extend to low- and middle-income countries, but also that potential perpetrators of reproductive coercion include in-laws [19],[20]. Moving beyond epidemiologic studies, recent research in the United States has described the development and evaluation of a reproductive health clinic-based intervention to reduce reproductive coercion in order to reduce unintended pregnancy [21].…”
Section: Reproductive Coercionmentioning
confidence: 99%
“…The survey was administered to women by female enumerators that were language and ethnically matched to the participant. Further study and related intervention information can be found elsewhere (Gupta et al, 2012). All study procedures were approved by the Yale School of Public Health and Innovations for Poverty Action Human Research Committees.…”
Section: Methodsmentioning
confidence: 99%
“…For example, a recent study documented that over one in four women participating in an economic programme reported any abuse from in-laws in their lifetime in rural Côte d’Ivoire (Gupta, Falb, Kpebo, & Annan, 2012). In global settings, such violence perpetrated by in-laws of women has been linked with a co-occurrence of IPV (Chan et al, 2009; Raj, Livramento, Santana, Gupta, & Silverman, 2006; Raj et al, 2010), and the co-occurrence of such violence has been documented in war-affected populations (Raj, Gomez, & Silverman, 2011); yet there have been few investigations into the risk factors related to victimisation from in-laws, particularly within war-affected areas.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation